Insights into phenol monomers in response to electron transfer capacity of humic acid during corn straw composting process. (15th August 2022) - Zhao, Xinyu; Zhang, Chuanyan; Dang, Qiuling; Xi, Beidou
Abstract: Quinone is the important redox functional group for electron transfer capacity (ETC) of humic acid (HA). Lignin, as major component in corn straw, can be decomposed into phenol monomers, then oxidation into quinones for synthesis of HA during composting process. However, it is still unclear that the effects of type and variation characteristics of phenol monomers on redox characteristics of HA during straw composting process. In this study, p-hydroxybenzoic acid (P1), vanillic acid (P2), syringic acid (P3), p-hydroxy benzaldehyde (P4), 4-coumaric acid (P5), 4-hydroxyacetophenone (P6), ferulic acid (P7) and 4-hydroxy-3-methylacetophenone (P8) were recognized and clustered into three groups. The concentration of polyphenol presented a significant downward trend during the straw composting process. Based on the relationships among phenol monomers to ETC, electron donating capacity (EDC), electron accepting capacity (EAC) and quinone, we found that P1, P2, P3, P5 and P7 were significantly related to ETC, EDC and EAC of HA ( P  < 0.05). Furthermore, NH4 + -N and NO3 − -N were the main micro-environmental factors linking to ETC-related phenol monomers and redox characteristics of HA in straw composts ( P  < 0.05). Finally, two groups of core microflora that promoting the ETC-related phenol monomers and NH4 + -N, and ETC-related phenol monomers and NO3 − -N were identified by Mantel test, respectively. This study contributes a new insight for polyphenol way for redox capacity of HA in traditional composting and utilization of straw compost in contaminated environments. Graphical abstract: Image 1 Highlights: Eight phenol monomers are identified during corn straw composting process. Five phenol monomers significantly related to the ETC of HA. ETC-related phenol monomers conversion is cooperated to NH4 + -N and NO3 − -N. Core microbes linking ETC of HA to ammonization and nitrification are selected.